In vitro Regeneration of Japanese Burdock (Arctium lappa L.) from Cotyledon and Leaf Derived Explants (Plant Tissue Culture and Biotechnology, 2022)
Considering the vegetable and medicinal values, a micropropagation protocol has been established for Japanese Burdock (Arctium lappa L.) by culturing the explants of cotyledon and leaf obtained from in vitro grown seedlings. Direct shoot regeneration was achieved from cotyledon and leaf explants on MS fortified with 4.0 μM BAP and 2.0 μM IBA or NAA after 5 weeks of culture. In addition, both the explants also formed callus from their cut margins within 6 weeks of cultivation on medium complemented with 6.0 μM BAP and 4.0 μM IBA or NAA. Adventitious shoots were also redeveloped through indirect organogenesis from the cotyledon and leaf-derived callus within 10 weeks of culture on MS containing 4.0 μM BAP and 2.0 μM IBA or NAA. The highest rate of shoot reproduction was attained at the third subculture, and more than 12.6 shoots were formed per callus clump. Within 4 weeks of transfer to the rooting medium on MS containing 6.0 μM IBA, the cultured micro-shoots produced highest 5.3 roots per cultured shoot. Rooted plantlets were successfully established on a soil-composed-sand mixture under natural condition with 93.3% survival ratePlant Tissue Cult. & Biotech. 31(2): 123-134, 2021 (December)